Compensation packages and implications for social networks among development-induced displaced persons in Uganda's Albertine Graben. Issue 6 (18th August 2021) - Mugagga, Frank; Tibakunirwa, Leonida; Musali, Paul
ABSTRACT: The study aimed at understanding the implications of compensation packages for the social networks of displaced persons in Uganda's oil-rich Albertine Graben. Questionnaires, interviews, focus group discussions, and observations were used to obtain data from purposively selected respondents. Qualitative data was analysed using content analysis while quantitative data analysis entailed generating descriptive statistics (percentages) and inferential analysis was performed through cross-tabulation by way of chi-square tests. There was a significant association between compensation type and social network distortion for the affected groups ( p = 0.000). Institutional management of different compensation packages exhibited professional shortcomings that need to be addressed to build sustainable social networks such as credit facilities. We thus recommend that government involves all stakeholders at every development phase and that compensation rates are continuously updated to allow for fair compensation rates in future and effective resettlement procedures during induced-displacement and resettlement processes.